Acute lung inflammation induced by zinc oxide nanoparticles: Evolution and intervention via NRF2 activator. (April 2022) - Guo, Tingyue; Fang, Xin; Liu, Yiting; Ruan, Yihui; Hu, Yu; Wang, Xuening; Hu, Yuxin; Wang, Gang; Xu, Yuanyuan
Abstract: Zinc oxide nanoparticles (ZnONPs) are widely used worldwide. Human inhalation exposure to ZnONPs induces acute lung inflammation (ALI); however, the characteristics and therapeutic targets of ALI are unclear. In this study, female C57BL/6J mice were subjected to a single intratracheal instillation of 20 μg of ZnONPs. Increased lung malondialdehyde levels and decreased total antioxidant capacity at 6 h, as well as increased lactate dehydrogenase levels in bronchoalveolar lavage fluid (BALF) at 1 day (d) post treatment were observed. A significant inflammatory response was observed at 3 d and 7 d, as evidenced by increased leukocyte numbers and total protein concentration in BALF, and histological abnormalities. Pulmonary NRF2 signaling was significantly activated at 3 d post treatment. To investigate a protective role of NRF2 activator against ZnONP-induced ALI, the mice were intraperitoneally injected with 2-cyano-3, 12-dioxooleana-1, 9-dien-28-imidazolide (CDDO-Im) (2 mg/kg) 1 d before and 1 d after ZnONPs treatment. CDDO-Im significantly decreased leukocyte numbers and total protein concentration in BALF and pulmonary inflammatory gene expression, and ameliorated histopathological abnormalities induced by ZnONPs. Collectively, the present study indicates that ZnONPs exposure leads to oxidative stress, cell injury and inflammation in the lung successively. Moreover, the NRF2 activator protects against ZnONPs-induced ALI. Graphical abstract: Image 1 Highlights: Exposure to ZnONPs induces lung oxidative stress, cell injury and subsequent acute lung inflammation (ALI). NRF2 is activated by ZnONPs exposure. NRF2 activator, CDDO-Im, significantly ameliorates ZnONPs-induced ALI.